Inter-individual association levels correlate to behavioral diversity in coastal bottlenose dolphins (Tursiops truncatus) from the Southwestern Gulf of Mexico - García Vital, Marah; Morteo Ortiz, Eduardo; Martínez Serrano, Ibiza; Delgado Estrella, Alberto; Bazúa Durán, María del Carmen (THERYA, 2015)
Introduction: Societies in mammal species are influenced by intrinsic and extrinsic factors that affect the temporality of the associations among individuals. Coastal bottlenose dolphins generally live in small fluid aggregations variable in composition, but the nature of their associations is commonly unknown. Our goal was to determine if school size was influenced by dolphins’ behavior, and if individuals associated to develop particular activities within the coastal waters of Alvarado, Mexico. Methods: In total, 80 boat-based surveys were conducted (2002 - 2003 and 2006 - 2009), where group size, behavior, and photo-identification data were collected. From 237 sightings and 2,021 dolphins the mean school size was 8.5 animals (s. d. = 8.6), but individuals and pairs were observed more frequently (33 %). Results: Temporal differences in school sizes and behavior conveyed with habitat seasonality (P < 0.05), but were inconsistent across years; thus short-term factors such as marine traffic and fisheries intensity were deemed important. Dolphins were commonly feeding (29 %) corresponding to groups of 4 - 6 animals, whereas solitary individuals typically showed evasion (P < 0.01). Discussion and Conclusions: Association coefficients computed for 89 of the 232 identifiable dolphins proved not random only in 6 % of the 3,915 combinations (P < 0.05), and these coefficients were positively correlated to the diversity of activities developed by each dyad (P < 0.01), thus the nature of their associations in most cases (93 %) became richer with time. The community is likely formed by very small units that frequently exchange members; this may be due to large food availability and low predator abundance in the area, but also to avoid detection and threats posed by local artisanal fisheries. Key words: Avoidance; behavior; group size; membership; socialization; fisheries.